Truthfulness and Business - Radoilska, Lubomira (Journal of business ethics, 2008)
According to a common assumption, truthfulness cannot have an intrinsic value in business. Instead, it is considered only instrumentally valuable for business, because it contributes to successful trust-building. Some authors deny truthfulness even this limited role by claiming that truth-telling is not an essential part of business, which is a sui generis practice like poker. In this article, I argue that truthfulness has indeed an intrinsic value in business and identify the conceptual confusions underlying the opposite view. My account of truthfulness as a virtue shows that truthfulness is both valuable for its own sake and instrumental to further valuable goals. It helps pinpoint the implicit contradiction in claiming that truthfulness has an instrumental value only. I then challenge the reasons for considering business exempt from the constraints of truthfulness and elaborate on the analogy between game and business, which in fact supports instead of undermining my claim that business is a truthful practice. Finally, I illustrate my argument with a case study of the current crisis of trust faced by the pharmaceutical industry.